KONTRIBUSI PENDAPATAN TENAGA KERJA PEREMPUAN PEDAGANG SAYURAN TERHADAP PENDAPATAN KELUARGA DI PASAR BERSEHATI MANADO (Contribution of Female Vegetable Traders to Family Income in Pasar Bersehati Manado) - Cindy Anastasia Tiwa; Joachim N. K. Dumais; Sherly G. Jocom (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2023)
The research aims to determine the contribution of female vegetable traders' income to the to-tal family income and the time allocation of female vegetable traders in Pasar Bersehati Manado. The sampling method was purposive sampling. The population in this study was all female vegetable traders in Pasar Bersehati Manado, totaling 150 people. The sample size as respondents was 15 fe-male vegetable traders who met the criteria of having a complete family, including a husband, chil-dren (part of the family's dependents), and being a permanent trader.The results showed that the contribution of female vegetable traders' income to family income in Pasar Bersehati Manado was high, namely 45.60 percent, with an average income of Rp. 3,846,000/month. The majority of the time allocation of vegetable traders in Pasar Bersehati was spent on selling vegetables, which accounted for 49.70 percent with an average of 11.93 hours/day.